Sustainable MSME Empowerment Strategy in the Green Economy Era: An Analysis of the Influence of Excellent Service and Promotion on Consumer Purchasing Decisions - Rizky Muyasar; Hasanudin Hasanudin; Zalfa Siva Savira Ridwan (Universitas KH. Abdul Chalim Mojokerto, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in maintaining Indonesia’s economic stability through their ability to create employment opportunities, enhance community welfare, and strengthen national economic independence. The contribution of MSMEs to the Gross Domestic Product (GDP) and employment absorption demonstrates that this sector serves as a fundamental pillar of Indonesia’s economic system. However, in the era of the green economy, MSMEs are required to adapt to sustainability principles to remain competitive. Two key aspects that support this sustainability are the implementation of excellent service and effective promotional strategies, as both significantly influence consumer purchasing decisions and maintain business competitiveness. This study adopts a quantitative approach with an associative method. Data were collected through questionnaires distributed to retail MSME actors and consumers in Karang Asem Barat Subdistrict, Citeureup District, Bogor Regency. The data were analyzed using linear regression with SPSS version 26 to examine the effect of excellent service and promotion on purchasing decisions. The results show that Excellent Service (X1) has a positive and significant effect on purchasing decisions, indicating that fast, friendly, and accurate service increases consumer comfort and loyalty. Promotion (X2) also has a significant effect, as promotional strategies tailored to consumer needs encourage purchasing behavior. The simultaneous test (F-test) reveals that both variables jointly have a significant influence on purchasing decisions. The Adjusted R² value of 0.599 indicates that excellent service and promotion explain 59.9% of the variation in purchasing decisions, while the remaining 40.1% is influenced by other factors outside the model, such as price, product quality, and brand image. The findings of this study emphasize that strengthening excellent service and implementing innovative promotional strategies are key factors in enhancing competitiveness and ensuring the sustainability of MSMEs in the green economy era.